Contributing to Multi-Sector Displacement of Vulnerabilities to Radicalization through a Developmental Evaluation Approach (Ottawa, Canada) - Chad Nilson; Julie McKercher (Proceedings, 2021)
This presentation introduces workshop participants to the role of developmental evaluation in multi-sector collaborative efforts to detect and displace vulnerabilities to the risk of violent extremism. Our discussion shares the journey that the Ottawa Police Service took to mobilize a wide variety of human service partners under a shared commitment to work upstream—where there is an opportunity to support individuals and families during early signs of vulnerability to radicalization. The result of this collaboration is the Ottawa Vulnerability Reduction Protocol: a multi-sector prevention tool aimed at identifying opportunities to support individuals before vulnerability for risk of radicalization to violence occurs. The protocol helps human service professionals, who may not have expertise in violent extremism, to develop the capacity, opportunity, and confidence to contribute towards upstream solutions. Participants of test simulations describe the protocol as allowing for support to be mobilized without labeling and stigmatizing an individual (i.e., radical, extremist), while also requiring the types of support that most human service professionals are comfortable providing. Construction of the protocol and accompanying resources (e.g., Vulnerability Detection Tool, Shared Needs Assessment, Integrated Support Plan) was supported through a developmental evaluation framework. By incorporating the continuous collection of data, ongoing stakeholder feedback, and insight from the preventing and countering violent extremism field, the evaluator assisted community partners in determining a structure and approach to building the protocol. This developmental evaluative approach helped diverse human sectors to navigate multiple perspectives and identify a shared pathway forward.